Iowa RBA, May 6, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for May 6, 1996. Highlights of the update include sightings of a Neotropic Cormorant, twenty White-faced Ibis, an immature Little Blue Heron, Cinnamon Teal, Red-necked Grebe, Bewick's Wren and a Snowy Egret. Also included are handwritten notes for the next week's update with sightings of an adult Mute Swan, Ruddy Turnstone and a Yellow-crowned Night Heron. Epson - sheet feed/flatbed